Uniform MnCo2O4.5 porous nanowires and quasi-cubes for hybrid supercapacitors with excellent electrochemical performances. Issue 15 (25th June 2021) - Du, Xuming; Sun, Jiale; Wu, Runze; Bao, Enhui; Xu, Chunju; Chen, Huiyu
Abstract : A simple hydrothermal route with a post annealing treatment was used to prepare MnCo2 O4.5 porous nanowires and quasi-cubes with excellent electrochemical performances. Abstract : In this work, uniform MnCo2 O4.5 nanowires (NWs) on stainless steel foil (SSF) were prepared through a facile, cost-efficient, and eco-friendly hydrothermal method at 120 °C with a post-calcination process in air. The microstructure of MnCo2 O4.5 samples could be tuned at different hydrothermal temperatures and quasi-cubes (QCs) were obtained in high yield at 150 °C. The MnCo2 O4.5 NW powder peeled off from the SSF delivered an outstanding capacity of 248.62 C g −1 at 1 A g −1 with a capacity preservation of 179.43 C g −1 at 8 A g −1, while the QCs exhibited 177.19 and 111.73 C g −1, respectively. To assess the possibility of its actual applications, a hybrid supercapacitor (HSC) device has been assembled by utilizing these MnCo2 O4.5 NWs (QCs) and activated carbon (AC) as the cathode and anode, respectively. The MnCo2 O4.5 NWs//AC HSC delivered a maximum capacity up to 116.95 C g −1 and extraordinary cycling durability with only 3.56% capacity loss over 5000 cycles. Besides, the MnCo2 O4.5 NWs//AC HSC achieved a maximum energy density of 25.41 W h kg −1 at a power density of 782.08 W kg −1, and for the QC-based HSC, it showed a lower energy density of 20.54 W h kg −1 at 843.34 W kg −1 . These remarkable electrochemical properties demonstrate that the porous MnCo2 O4.5 NWs and QCs may serve as promising cathodes for advanced hybrid supercapacitors with superior performance, and the present synthetic methodology may be applied to the preparation of other cobalt-based binary metal oxides with excellent electrochemical properties.